Pengaruh Senam Fantasi dengan Perkembangan Motorik Kasar Anak Usia Prasekolah di TK Maraqitta’limat Memben Daya - Fibrianti Fibrianti; Eka Faizaturrahmi; Baiq Disnalia Siswari; M. Jumaidi Sapwal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
According to the 2016 World Health Organization report, 250 million preschool children cannot develop their full developmental potential, which includes motor, physical, socio-emotional, and cognitive development. The negative effects of not providing children with stimulation and stimulation on gross motor skills can result in children having difficulty walking, frequently falling when jumping, and being unable to control other muscle movements.to know the effect of fantasy gymnastics on the development of gross motor skills in preschool-age children at Maraqitta'limat Memben Daya Kindergarten in 2022. This research is a quantitative study with a pre-experimental approach. This research was conducted in September 2022 at the Maraqitta'limat Memben Daya Kindergarten. The population in this study was all preschool-age children in the Maraqitta'limat Memben Daya Kindergarten, consisting of 17 respondents. In this study, the sampling technique used was the total sampling technique. There is an effect of fantasy gymnastics on the gross motor development of preschool children at Maraqitta'limat Memben Daya Kindergarten in 2022 with a p-value of 0.0010.05. The conclusion of this study is that there is an effect of fantasy gymnastics on the gross motor development of preschool-age children at Maraqitta'limat Memben Daya Kindergarten in 2022